2022
DOI: 10.3102/00028312221079297
|View full text |Cite
|
Sign up to set email alerts
|

Separate Remains Unequal: Contemporary Segregation and Racial Disparities in School District Revenue

Abstract: Resource exposure was a key mechanism linking patterns of racial segregation and student outcomes during the Brown v. Board of Education era. Decades later, past progress on school desegregation may have stalled, raising concerns about resource equity and associated student outcomes. Are recent trends in segregation associated with racial disparities in district revenue? Drawing on national data from the School Funding Fairness Data System and the Common Core of Data, this study examines the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Weathers and Sosina report that more racial segregation is associated with larger racial disparities in school revenue, net of racial socioeconomic segregation (measured by the extent of child poverty). 79 When one looks at school districts that are either predominantly Black or predominantly white, the disparity in resources is more marked. EdBuild has compiled statistics from the 2015-16 school year on the resources available to districts that are greater than 75 percent white compared to districts that are 75 percent Black.…”
Section: A) Rationalization and The Racialization Of Education Perfor...mentioning
confidence: 99%
“…Weathers and Sosina report that more racial segregation is associated with larger racial disparities in school revenue, net of racial socioeconomic segregation (measured by the extent of child poverty). 79 When one looks at school districts that are either predominantly Black or predominantly white, the disparity in resources is more marked. EdBuild has compiled statistics from the 2015-16 school year on the resources available to districts that are greater than 75 percent white compared to districts that are 75 percent Black.…”
Section: A) Rationalization and The Racialization Of Education Perfor...mentioning
confidence: 99%
“…Segregation is an ethical and moral issue because it perpetuates and reflects a national legacy of racial and ethnic discrimination (Rosiek & Kinslow, 2015). Empirically, school segregation is a powerful predictor of disparities in academic achievement and resource provision (Berends & Penaloza, 2010; Palardy et al, 2015; Spatig-Amerikaner, 2012; Weathers & Sosina, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though it has been more than 60 years since the courts ruled that state-sanctioned segregated schools were unconstitutional (e.g., Brown v. Board of Education , 1954; Méndez v. Westminster School District , 1947 ) , racial, socioeconomic, and linguistic segregation continue to shape the experiences of American public school students (Marcotte & Dalane, 2019; Orfield et al, 2016; Owens et al, 2016), perpetuating inequitable access to educational opportunities (Berends & Penaloza, 2010; Spatig-Amerikaner, 2012; Weathers & Sosina, 2022). As districts have been released from federally mandated desegregation plans and, in many cases, experienced resegregation (Fiel & Zhang, 2019; Reardon et al, 2012), the role of local actors in countering segregation has become increasingly important.…”
mentioning
confidence: 99%
“…K-12 education finance policies in the United States are ostensibly “colorblind”—school funding is a responsibility of state governments, and none of the funding policies adopted by these governments explicitly considers race. However, for decades researchers have documented racial disparities in school funding (Baker & Green, 2005; Baker et al, 2020; Carey, 2004; EdBuild, 2019; Sosina & Weathers, 2019; Stiefel et al, 2005; Weathers & Sosina, 2019). To explain this pattern, scholars often focus on the way racial and economic segregation between school districts can impact inequities in local education funding (e.g., EdBuild, 2019).…”
Section: Background On Racial Disparities In School Fundingmentioning
confidence: 99%
“…According to one estimate, predominately non-student of color, high-poverty school districts received, on average, $23 billion more in education funding than predominately student of color, high-poverty districts during the 2015 to 2016 school year (EdBuild, 2019). Examining trends between 1999 and 2013, Weathers and Sosina (2019) and Sosina and Weathers (2019) found that increases in racial segregation are associated with increases in racial disparities in school district revenue and expenditures.…”
mentioning
confidence: 99%